Επικοινωνία γονέων παιδιών με ειδικές εκπαιδευτικές ανάγκες ή/και αναπηρίες και εργαζομένων στην ειδική αγωγή - Τσιμπιδάκη Ασημίνα (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The target of this research is to depict the views of professionals in special education related to the communication they develop with parents raising a child with special educational needs. More specifically, the study examines the form, the frequency, the difficulties that occur in communication process, and their proposals for an effective communication. This study constitutes a qualitative survey with quantitative comparative elements. The sample were 60 professionals in special education. Data were collected with the use of a structured interview. The findings indicate that communication is a continuous contact and exchange of information. The mother is the key person who comes in contact with the professionals. Professionals don’t testify with certainty whether the parents are cooperative, however, they indicate satisfaction with the fact that parents follow their instructions and advice. They communicate with parents on a regular basis, even though a specific workplace doesn’t exist, and they mention many efforts and actions for an effective communication. The main communication axis is the child with special educational needs itself. Also, they refer various boundaries in the communication process and, at the same time, they suggest effective ways aiming to resolve these difficulties.